The cost-effectiveness of metformin in pre-diabetics: a systematic literature review of health economic evaluations. (3rd March 2020) - Gebregergish, Samron Brhane; Hashim, Mahmoud; Heeg, Bart; Wilke, Thomas; Rauland, Marco; Hostalek, Ulrike
ABSTRACT: Objectives : Our aim was to systematically identify and appraise cost-effectiveness studies of metformin in prediabetic subjects. Methods : A systematic literature review was conducted and reported according to standard guidlines. The search was conducted in PubMed, Embase, International Society for Pharmacoeconomics and Outcomes Research (ISPOR) presentation database and the Cost-Effectiveness Analysis (CEA) and Center for Reviews and Dissemination (CRD) registries. All cost-effectiveness studies assessing metformin in prediabetic patients were included. Results : Twenty-three reports were included. Metformin and intensive lifestyle changes (ILC) interventions were always cost-effective compared to placebo. ILC was cost-effective and sometimes dominant compared to metformin. Metformin was cost-saving compared to ILC in the short and medium-term. Although, in the long term, metformin was more expensive than ILC in terms of direct medical costs, when indirect non-medical costs are included, metformin less expensive than ILC. One study reported that for patients with Body Mass Index (BMI) higher than 30 kg/m2, metformin is a cost-effective strategy compared to placebo and ILC. However, this finding was not confirmed by other retrieved studies. Conclusion : ILC is cost-effective compared to metformin and, both of them are cost-effective compared to placebo. Metformin may be cost-saving in the short- to medium-term and possibly in the long-term.